Schwann Cells Accelerate Osteogenesis via the Mif/CD74/FOXO1 Signaling Pathway In Vitro - Jun-Qin Li; Hui-Jie Jiang; Xiu-Yun Su; Li Feng; Na-Zhi Zhan; Shan-Shan Li; Zi-Jie Chen; Bo-Han Chang; Peng-Zhen Cheng; Liu Yang; Guo-Xian Pei (Stem Cells International)
Schwann cells have been found to promote osteogenesis by an unclear molecular mechanism. To better understand how Schwann cells accelerate osteogenesis, RNA-Seq and LC-MS/MS were utilized to explore the transcriptomic and metabolic response of MC3T3-E1 to Schwann cells. Osteogenic differentiation was determined by ALP staining. Lentiviruses were constructed to alter the expression of Mif (macrophage migration inhibitory factor) in Schwann cells. Western blot (WB) analysis was employed to detect the protein expression. The results of this study show that Mif is essential for Schwann cells to promote osteogenesis, and its downstream CD74/FOXO1 is also involved in the promotion of Schwann cells on osteogenesis. Further, Schwann cells regulate amino acid metabolism and lipid metabolism in preosteoblasts. These findings unveil the mechanism for Schwann cells to promote osteogenesis where Mif is a key factor.